Investigating Of Using Teacher Talk Strategy To Build Students' Participation And Motivation In English Speaking Class - Novitasari; Muhamad Arief; Riki Ruswandi; Hamdan Hidayat (Yayasan Sahabat Literasi Edukasi dan Publikasi Bandung, 2025)
Speaking English is about practice. A lack of motivation in learning can become a challenge for both students and teachers. Insufficient participation and interaction between teachers and students lead to an ineffective learning process. Communication is the key to connecting the learning process and its outcomes. Teacher talk is a verbal communication strategy that plays an essential role in the ongoing learning process. This research aims to identify the types of teacher talk frequently used by teachers and the factors influencing student participation and motivation in English-speaking classes. This study used a qualitative approach with a phenomenological method as a research design. The participants of this study were English teachers and seventh-grade students from two different private junior high schools, namely SMP KP 2 Majalaya and SMP Nusantara. The data for this study were obtained from interviews, observations, questionnaires, and documentation. The data analysis technique used was descriptive analysis. The results showed that seventh-grade English teachers at SMP KP 2 Majalaya 100% frequently used the categories of praising, encouraging, and asking. Meanwhile, seventh-grade English teachers at SMP Nusantara 100% often use the categories of giving information and criticizing students. The three highest percentages of factors influencing students' participation and motivation in learning English show that 62% of students are happy with the way teachers give responses and corrections. Then 60% of students are happy when the teacher appreciates and encourages students through motivational words and praise. And 55% of students were happy with the way the teacher delivered the material